Safety reporting and adverse-event profile of mirtazapine described in randomized controlled trials in comparison with other classes of antidepressants in the acute-phase treatment of adults with depression: systematic review and meta-analysis. - Watanabe, N; Omori, I; Nakagawa, A; Cipriani, A; Barbui, C; McGuire, H; Churchill, R; Furukawa, T (2010)
BACKGROUND: Mirtazapine has a unique mechanism of antidepressant action, and thus is thought to have a different profile of adverse events from that of other antidepressants. OBJECTIVE: To present a methodologically rigorous systematic review of the adverse event profile of mirtazapine and point to possible problems with safety reporting in randomized controlled trials (RCTs) of the acute-phase treatment of major depression in adults with mirtazapine in comparison with other types of antidepressant. METHODS: The Cochrane Collaboration Depression, Anxiety and Neurosis Controlled Trials Register was electronically searched using the following search terms: 'depress*', 'dysthymi*', 'adjustment disorder*', 'mood disorder*', 'affective disorder', 'affective symptoms' and 'mirtazapine'. Pharmaceutical companies and experts in this field were contacted, and the reference lists of the relevant RCTs were checked, for additional data. No language restriction was imposed. Two authors independently assessed the quality of trials for inclusion in the review. Disagreements were resolved by consensus. Two authors independently extracted data on adverse events. Disagreements were resolved by consensus. The adequacy of safety reporting was assessed by one author. Regarding the adequacy of safety reporting, the qualitative and quantitative parameters of safety reporting were determined. Regression analyses were conducted to assess characteristics of trials influencing safety reporting. The primary and secondary outcomes in the systematic review of the adverse events associated with mirtazapine were defined as the proportion of patients having each of 43 adverse events listed in the modified version of the WHO Adverse Reaction Terminology, and the proportion of patients experiencing at least one adverse event, respectively. Meta-analyses were conducted for these outcomes. RESULTS: Twenty-five RCTs involving 4842 patients were identified as meeting our inclusion criteria. With regard to safety reporting, only two trials and no trials were rated as 'adequate' in terms of the reporting of clinical adverse events and laboratory-determined toxicity, respectively. The proportion of text in the results sections of the study reports devoted to safety reporting was a mean of 22%. No associations were observed between the adequacy of safety reporting and any characteristics of the trials; however, sample size over 100 participants in total and over 50 subjects in a study arm, double blindness and sponsorship by the company marketing mirtazapine were significantly associated with a greater number of reported adverse events in mirtazapine recipients. In terms of individual adverse events, mirtazapine was significantly less likely to cause hypertension or tachycardia (risk ratio [RR] 0.51) and tremor (RR 0.43) than tricyclic antidepressants (TCAs). In comparison with selective serotonin uptake inhibitors (SSRIs), mirtazapine was significantly more likely to cause weight gain or increased appetite (RR 3.68), increased salivation (RR 3.66), somnolence (RR 1.62) and fatigue (RR 1.45), but less likely to cause flatulence (RR 0.26), sweating (RR 0.28), sexual dysfunction (RR 0.34), tremor (RR 0.37), nausea or vomiting (RR 0.40), sleep disturbance (RR 0.55) and diarrhoea (RR 0.61). In comparison with the serotonin-noradrenaline (norepinephrine) reuptake inhibitor (SNRI) venlafaxine, mirtazapine was significantly more likely to cause fatigue (RR 2.02), but less likely to cause sleep disturbance (RR 0.03), sweating (RR 0.03) and constipation (RR 0.25). Relative to trazodone, mirtazapine was significantly more likely to cause weight gain or increased appetite (RR 4.00). Approximately 70% of patients treated with mirtazapine experienced at least one adverse event, with no significant difference in comparison with other antidepressants. CONCLUSIONS: The study confirmed the paucity of adequate safety reporting in trials comparing mirtazapine with other types of antidepressant in the acute-phase treatment of depression in adults. Based on the available evidence, mirtazapine appears to have a unique adverse-event profile. Using these findings, clinicians can inform their patients, not only of the simple frequency of adverse events with mirtazapine, but also of the relative difference in the frequency of adverse events in comparison with that of other antidepressants, to aid pragmatic clinical decisions.